2003
DOI: 10.1016/s0048-9697(02)00477-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of potassium chloride to a Chernobyl-contaminated lake: modelling the dynamics of radiocaesium in an aquatic ecosystem and decontamination of fish

Abstract: This study tests a whole-lake experiment to reduce the bioaccumulation of radiocaesium (137Cs) in fish in lakes contaminated by the Chernobyl accident. In many lakes in the Chernobyl contaminated areas, radiocaesium activity concentrations in fish are still significantly higher (up to 100 times in some species) than acceptable limits for human consumption. Estimates of the long-term rate of decline of 137Cs in fish in these regions, in the absence of countermeasures, show that radioactivity in fish in some lak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 12 publications
(20 reference statements)
1
15
1
Order By: Relevance
“…This CF range also corresponds with the data published by other authors, e.g. Smith et al (2002Smith et al ( , 2003, found the CF values in the range between 0.1 and 10 m 3 /kg. The data set of 90 Sr was insufficient for assessing the trends in the 90 Sr concentration.…”
Section: Fishsupporting
confidence: 92%
“…This CF range also corresponds with the data published by other authors, e.g. Smith et al (2002Smith et al ( , 2003, found the CF values in the range between 0.1 and 10 m 3 /kg. The data set of 90 Sr was insufficient for assessing the trends in the 90 Sr concentration.…”
Section: Fishsupporting
confidence: 92%
“…The ratio of 137 Cs atoms displaced to the number of 133 Cs atoms added in Pond 4 was greater than the ratios of 137 Cs atoms displaced to K atoms added in Lake Kostiukovichy (Smith et al, 2003) where the addition of 1.0!10 29 K atoms resulted in the displacement of approximately 5.2!10 18 137 Cs atoms in the first year following the addition. An approximate ratio of one 137 Cs atom displaced per 1.9!10 10 K atoms.…”
Section: Discussionmentioning
confidence: 71%
“…The addition of K to Lake Kostiukovichy (Smith et al, 2003) was performed to test the effectiveness of K additions as a remediation technique to reduce 137 Cs concentrations in biota. The K addition resulted in a 10-fold increase in K concentrations and a 50% reduction in 137 Cs concentrations in fish despite a 3-fold increase in 137 Cs concentrations in the water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations